IMPLEMENTASI CYBER PUBLIC RELATIONS AKUN @BADANKESBANGPOL.KOTATANGERANG DALAM OPTIMALISASI PELAYANAN INFORMASI PUBLIK - Salma Aprilianti; Lathifa Prima Ghanistyana; Indah Rejeki; Anggun Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The advancement of digital technology has transformed the paradigm of public relations (PR), particularly within government institutions, through the implementation of Cyber Public Relations (Cyber PR). Official social media accounts now serve as a frontline tool for delivering information to the public in a fast, interactive, and transparent manner. This study aims to analyze the implementation of Cyber PR strategies by the Instagram account @badankesbangpol.kotatangerang in supporting the optimization of public information services. This research adopts a descriptive qualitative approach, using digital observation, in-depth interviews, and documentation as data collection techniques. Observations were conducted on the account’s posts and interactions over the past six months, while interviews involved account administrators and public followers. The data were analyzed using Miles and Huberman’s interactive analysis model, involving data reduction, presentation, and conclu sion drawing. The findings reveal that the account has implemented Cyber PR elements through visual information delivery, consistent posting, and active interaction with followers. However, public participation remains largely passive (likes and views), with limited two-way substantive feedback. The communication strategy tends to be one-way, although the visual style and language align with digital media characteristics for government communication. It is concluded that the implementation of Cyber PR on the account contributes positively to public information transparency, though improvements in public engagement and participatory interaction are still needed. Developing dialogic content and encouraging citizen involvement are strategic steps moving forward.